Palestine and the Great Powers, 1945-1948 - Cohen, Michael J. (Book collections on Project MUSE., 2014)
Cohen examines the struggle leading to the creation of the state of Israel, placing British evacuation of Palestine in the context of Britain's postwar weakness. The author describes the policies and character of each of the major actors in his story--Bevin. Truman. Ben-Gurion, and the Mufti of Jerusalem. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts.